Virtual scene generation promotes shadow puppet art conservation - Liang, Hui; Dong, Xiaohang; Pan, Junjun; Zheng, Xiangyu (Computer animation and virtual worlds, 2023)
As an ancient performing art, shadow puppetry is a treasure of Chinese art. However, with the development of society, shadow puppetry becomes less well‐known among the young generation. To preserve and further spread this traditional culture, the digitization of shadow puppets is playing an increasingly important role in shadow puppetry conservation. Despite this, the spread of shadow puppetry culture in modern times still faces many hindrances. In digitalized shadow puppet art, the virtual scenes in certain degree determine the artistic effect of shadow puppet performance. The commonly used method for digital shadow puppet scene construction is via artificially created models which are then placed in corresponding positions. Obviously, this is a cumbersome and time‐consuming task. Therefore, a semantic‐based scene generation method for digital shadow puppet performance scene is proposed in this paper. According to this method, the key information is extracted from the descriptive text using the Chinese text segmentation technology. Meanwhile, we generate semantic scene graphs and search the corresponding shadow puppet models in the model library to construct the virtual scenes of digital shadow puppet performance. In the evaluation experiment, we invited 30 volunteers (10 female and 20 male) who had been exposed to traditional shadow puppet play in their daily lives. As suggested by the experimental results, the digital shadow puppet performance scene generated in this paper exhibit advantages of convenient use and high availability, which largely enhance the effect of digital shadow puppet performance. It should nonetheless be noted that it's not easy to extract the spatial relations from complicated texts, which inevitably limits the effectiveness of our scene generation method. The research work of this paper aims to promote digital shadow puppet technology and provide insights for the inheritance and conservation of traditional shadow puppet art.